Phytochemical Analysis, FTIR Spectroscopic of Flavonoid and Antibacterial Activity of Crassocephlum Crepidiodes (Benth.) S. Moore Leaf and Herbs Extract - Sari, Retno Komala; Susilowati, Susilowati; Wahyudi, Didik (GLOBAL HEALTH SCIENCE GROUP, 2024)
Staphylococcus aureus is a bacteria that causes various skin diseases. C. crepidiodes contains flavonoid compounds which are thought to be responsible for antibacterial activity. This research aims to identify flavonoid compounds and antibacterial activity in the leaves (LC) and herbs (HC) of C. crepidiodes. LC and HC were extracted with 70% ethanol using the maceration method. The secondary metabolites were evaluated by phytochemical analysis and flavonoid compound identification using the Spectrophotometer Fourier Transform Infra-Red (FTIR) test and the antibacterial activity was conducted by the Well method against S. Aureus. The results showed that the secondary metabolite compounds of LC were different from HC and the differences FTIR spectra in transmittance peaks in the identified functional group hydroxyl stretching vibrations correlate with the antibacterial activity of S. Aureus. The antibacterial activity test of C. crepidiodes leaf extract had an average inhibitory zone concentration of 8.35mm to 15.09mm. In comparison, herbal extracts had an average inhibitory zone of 13.61mm to 18.11mm. HC (average inhibitory zone of 13.61mm to 18.11mm) has greater antibacterial activity than LC (average inhibitory zone concentration of 8.35mm to 15.09mm). The herbs parts of C. crepidiodes can be recommended as active antibacterial natural ingredients. This understanding is important to improve the quality of traditional medicine raw materials.